The observed relationship of cloud to surface longwave radiation and air temperature at Ny-Ålesund, Svalbard. Issue 1 (1st January 2018) - Yeo, Huidong; Park, Sang-Jong; Kim, Baek-Min; Shiobara, Masataka; Kim, Sang-Woo; Kwon, Hataek; Kim, Joo-Hong; Jeong, Jee-Hoon; Park, Sang Seo; Choi, Taejin
Abstract: Ten-year (2004–2013) observations of cloud and surface shortwave (SW) and longwave (LW) fluxes at Ny-Ålesund were analysed to investigate monthly variations in cloudiness and their impacts on the surface LW radiation budget and near-surface temperature ( T s ). The cloud fraction (CF) showed distinct monthly variations, high in summer (0.90) and lower in winter (0.79). The downward SW flux increased from March and showed a peak (~200 W m −2 ) in June. In contrast, the downward LW (LWD) flux increased from ~200 W m −2 in February to ~300 W m −2 in July. Both LWD and upward LW (LWU) fluxes and their difference increased during winter as lowest cloud base height (LCBH) decreased and CF increased. T s difference and both LW fluxes difference (ΔLWD and ΔLWU), calculated as the difference in monthly mean T s and LW between all-sky and cloud-free conditions, were highly correlated ( R 2  = 0.68 for LWD and R 2  = 0.92 for LWU). Dramatic changes in T s, CF and LW fluxes at Ny-Ålesund were closely associated with cold and warm air mass advection on a multi-day time scale. The average T s under low-level clouds (LCBH ≤ 2 km) was estimated as −7.4 ± 6.1 °C due to warm air masses advected from the North Atlantic Ocean and Barents Sea, whereas the average T s on cloud-free days was −14.5 ± 5.7 °C because of cold air mass advection from the pole. However, the duration of low-level clouds may not be long enough to drive such large T s variations. 75-percentile of low-level cloud conditions at Ny-Ålesund persisted up to 2.3 days, whereas cloud-free and high-altitude cloud (LCBH > 2 km) conditions lasted for approximately 0.8 and 0.5 days, respectively. This implies that cloud LW effects on several warm days may be larger than the monthly average, but may not be accumulated enough to induce surface warming due to abrupt T s drop associated with cold air mass advection.